Hypertriglyceridemia and Atherosclerosis: Using Human Research to Guide Mechanistic Studies in Animal Models - Basu, Debapriya; Bornfeldt, Karin E. (Frontiers in Endocrinology, 2020)
Human studies support a strong association between hypertriglyceridemia and atherosclerotic cardiovascular disease (CVD). However, whether a causal relationship exists between hypertriglyceridemia and increased CVD risk is still unclear. One plausible explanation for the difficulty establishing a clear causal role for hypertriglyceridemia in CVD risk is that lipolysis products of triglyceride-rich lipoproteins (TRLs), rather than the TRLs themselves, are the likely mediators of increased CVD risk. This hypothesis is supported by studies of rare mutations in humans resulting in impaired clearance of such lipolysis products (remnant lipoprotein particles; RLPs). Several animal models of hypertriglyceridemia support this hypothesis and have provided additional mechanistic understanding. Mice deficient in lipoprotein lipase (LPL), the major vascular enzyme responsible for TRL lipolysis and generation of RLPs, or its endothelial anchor GPIHBP1, are severely hypertriglyceridemic but develop only minimal atherosclerosis as compared with animal models deficient in apolipoprotein (APO) E, which is required to clear TRLs and RLPs. Likewise, animal models convincingly show that increased clearance of TRLs and RLPs by LPL activation (achieved by inhibition of APOC3, ANGPTL3 or ANGPTL4 action, or increased APOA5) results in protection from atherosclerosis. Mechanistic studies suggest that RLPs are more atherogenic than large TRLs because they more readily enter the artery wall, and because they are enriched in cholesterol relative to triglycerides, which promotes pro-atherogenic effects in lesional cells. Other mechanistic studies show that hepatic receptors (LDLR and LRP1) and APOE are critical for RLP clearance. Thus, studies in animal models have provided additional mechanistic insight and generally agree with the hypothesis that RLPs derived from TRLs are highly atherogenic whereas hypertriglyceridemia due to accumulation of very large TRLs in plasma is not markedly atherogenic in the absence of TRL lipolysis products.